NIGELLA SATIVA: A BIBLIOMETRIC STUDY OF THE LITERATURE ON HABBAT AL-BARAKAH - Anwar, Mumtaz Ali (Malaysian Journal of Library and Information Science, 2005)
This study carried out a bibliometric analysis of the literature on Nigella sativa (Habbat al-barakah or Black seed). The purpose was to study the periodic growth of literature, author patterns, topical focus, and geographic origin of literature on the subject. Twenty related databases and several online catalogues of libraries were searched to identify a final list of 530 citations. This data set was analyzed using various bibliographic characteristics. The findings show the increase in the volume of literature from 1971 onwards starting from one citation per year growing to 46 papers per year during the late 1990s. Most of the literature comes from Medical Sciences and Chemistry. A small core of authors contributed about one-third of the citations. Four-fifths of the citations are the result of collaborative work. About two-fifths of the papers are published by only 36 journals. India and Egypt are the leading contributors to this literature. English is the dominant language.